Sosialisasi Pengetahuan Mitigasi Bencana dan Rekomendasi Bangunan Perlindungan Evakuasi di Kelurahan Pasie Nan Tigo - Utami Dewi Arman; Afrilda Sari; Rafki Imani (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2021)
Pasie Nan Tigo Village, Koto Tangah District, is a fairly densely populated area and is located on the coast of the city of Padang. The location has a fairly high risk and level of vulnerability to a tsunami disaster. It is necessary to conduct socialization on earthquake and tsunami disaster mitigation in order to increase the capacity of residents to face the bad possibilities of disasters that may occur in the future. In addition to conducting socialization, the implementation team also conducted a survey to the location to assess several buildings that meet the requirements as an alternative evacuation protection building (ESB) for local residents, including Rusunawa Pasie nan Tigo, UMSB Lecture Building and Ruko Mekar Baru located in the village. With the implementation of this socialization activity, it is hoped that the high level of preparedness and ability of residents in efforts to mitigate earthquake and tsunami disasters can reduce the number of disaster victims in the future.